BREAST MILK, OMEGA-3, OMEGA-6 FATTY ACIDS AND PEDIATRIC NURSING APPROACH IN HOSPITAL ADMINISTRATION - Cabar, Huriye Demet; Taskaya, Gokay; Soyler, Nazli (Acta Scientiae et Intellectus, 2024)
The relevant literature is searched this article was aimed to give information about breast milk, Omega-3, Omega-6 Fatty Acids and Pediatric Nursing Approach in this article. For this reason, a literature search was made and an article of review type was written. The main focuses are the fatty acids, the effects of fatty acids on infant development, breast milk and omega fatty acids, the effect of consuming fish on breast milk fatty acids and the pediatric nursing approach in hospital management. As a result, increasing the omega-3, omega-6 fatty acid content in the mother’s milk will enable these essential fatty acids to pass through to the baby and contribute to the growth and development of the baby. Therefore, it is important to give mothers information about consumption of omega-3, omega-6 fatty acids in the nursing approach.